Management of Medically Compromised Prosthodontic Patients - Pratistha Ghimire; Pramita Suwal; Bishal Babu Basnet (International Journal of Dentistry)
The medical evaluation of patients considering prosthodontic treatment is a vital step in the treatment planning. The prosthodontist should be able to assess the inherent risks associated with the treatment of patients with systemic conditions. Many factors are associated with evaluating the patient’s health status and risk including the patient’s current and past medical and dental history, current and past use of medications, type of treatment, length of treatment, invasiveness of treatment, and degree of urgency of treatment. In this article, some of the systemic diseases like arthritis, cardiovascular diseases, endocrine disorders, hematologic and oncologic disease, neurologic disorders, bone disorders, pulmonary diseases, liver diseases, and chronic kidney disease that commonly affect aged individuals are reviewed. The prosthodontic considerations that should be taken care of while managing patients with these systemic conditions will also be discussed.